2018
DOI: 10.1098/rsob.180058
|View full text |Cite
|
Sign up to set email alerts
|

Epichromatin and chromomeres: a ‘fuzzy’ perspective

Abstract: ‘Epichromatin’, the surface of chromatin beneath the interphase nuclear envelope (NE) or at the surface of mitotic chromosomes, was discovered by immunostaining with a specific bivalent mouse monoclonal anti-nucleosome antibody (mAb PL2-6). ‘Chromomeres’, punctate chromatin particles approximately 200–300 nm in diameter, identified throughout the interphase chromatin and along mitotic chromosomes, were observed by immunostaining with the monovalent papain-derived Fab fragments of bivalent PL2-6. The specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…In 300 mM sucrose (3c,d), epichromatin staining is still prominent, but less well defined. Our conclusion is that, even under hyperosmotic conditions, surface chromatin 'exposes' a high density of nucleosome acidic patches in suitable geometric arrangement to bind mAb PL2-6 with high avidity [27][28][29]. conditions.…”
Section: Super-resolution Sted Imaging Of Sucrose and Nacl Congealed mentioning
confidence: 84%
See 3 more Smart Citations
“…In 300 mM sucrose (3c,d), epichromatin staining is still prominent, but less well defined. Our conclusion is that, even under hyperosmotic conditions, surface chromatin 'exposes' a high density of nucleosome acidic patches in suitable geometric arrangement to bind mAb PL2-6 with high avidity [27][28][29]. conditions.…”
Section: Super-resolution Sted Imaging Of Sucrose and Nacl Congealed mentioning
confidence: 84%
“…Figure 1(f,h) show that congealed mitotic chromosomes maintain the 'surface' staining with anti-H3S10p. We have previously shown that antiepichromatin antibody (PL2-6) staining overlaps and extends slightly outside H3S10p staining [26,28]. It is clear that, as with PL2-6 immunostaining, the H3S10p epitopes remain at (or near) the outer surface of the mitotic chromosome clusters, whether or not they are perturbed by hyperosmotic treatment.…”
Section: Acute Hyperosmotic Sucrose Stress Congeals Interphase Chromamentioning
confidence: 89%
See 2 more Smart Citations
“…The electron-dense chromatin in the nuclear periphery corresponds to the LADs identified in human fibroblasts using lamin DamID (Guelen et al, 2008), and is enriched in LINE repeats and several histone marks of transcriptionally inactive chromatin, such as lysine nine diand tri-methylated histone H3 (H3K9me2 and H3K9me3) (Guelen et al, 2008;Wen et al, 2009). The peripheral chromatin immediately adjacent to the nuclear envelope is known as "epichromatin" and can be visualized in cells from different species using a special bivalent mouse monoclonal antinucleosome antibody (mAb PL2-6), which binds to the acidic patch on nucleosomes (Olins and Olins, 2018). This suggests that the chromatin close to the nuclear lamina not only has a peculiar composition, but additionally harbors a unique nucleosome structure that is not seen elsewhere in the nucleus.…”
Section: Nuclear Periphery Vs Centermentioning
confidence: 99%